The Quality of Institutions and Organizational Form Decisions: Evidence from Within the Firm. Issue 2 (26th October 2016) - Lafontaine, Francine; Perrigot, Rozenn; Wilson, Nathan E.
Abstract : In many retail and service sectors, firms have to establish a physical presence in a geographic market to access customers there. In countries where the quality of institutions is low, this can put assets at risk. We use data on the operations of a multinational, multibrand hotel company to show that in environments where local institutions are weaker—as proxied mainly by the World Bank's Checks index—the company eschews direct ownership. Rather than increasing its reliance on franchising, as predicted by some models, the company relies more on another form of organization commonly used in this industry, namely management contracts. We explain these patterns by emphasizing how the quality of the institutional environment affects the cost of using equity‐based organizational forms, per arguments in the current literature, but also the cost of enforcing the terms of franchise contracts.